2015
DOI: 10.1128/aac.01032-15
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Initial Amikacin Dosage in Adults

Abstract: bWe report on the pharmacokinetics (PK) and pharmacodynamics (PD) of high-dose (>15 mg/kg of body weight per day) amikacin. A mean (standard deviation [SD]) maximum drug concentration in the serum (C max ) and 24-h area under the concentration-time curve (AUC 24 ) of 101 (49.4) mg/liter and 600 (387) mg · h/liter, respectively, were observed (n ‫؍‬ 73) with 28.0 (8.47) mg/kg/day doses. An initial amikacin dose of 2,500 mg in adults weighing 40 kg to 200 kg with therapeutic drug monitoring to adjust the mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Based on the PTA simulation, a minimum amikacin dose of 60 mg/kg administered once daily is expected to achieve the efficacy target of an fC max /MIC of Ն8 in 80% of pediatric patients weighing 8 to 70 kg, with a 97.5% probability and a safety target of Ͻ10 mg/liter in almost all patients. This dosing recommendation is consistent with other studies that suggest higher single daily doses of amikacin of Ն40 mg/kg in different patient populations, including pediatric cancer patients (7,19,(27)(28)(29). In 1998, the amikacin dose of 20 mg/kg administered once a day was recommended for immunocompromised pediatric patients, including those with cancer (10).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on the PTA simulation, a minimum amikacin dose of 60 mg/kg administered once daily is expected to achieve the efficacy target of an fC max /MIC of Ն8 in 80% of pediatric patients weighing 8 to 70 kg, with a 97.5% probability and a safety target of Ͻ10 mg/liter in almost all patients. This dosing recommendation is consistent with other studies that suggest higher single daily doses of amikacin of Ն40 mg/kg in different patient populations, including pediatric cancer patients (7,19,(27)(28)(29). In 1998, the amikacin dose of 20 mg/kg administered once a day was recommended for immunocompromised pediatric patients, including those with cancer (10).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, amikacin, an aminoglycoside antibiotic used either alone or in combination with ␤-lactams to treat serious Gram-negative infections, was first approved at 15 mg/kg of body weight in 1 to 3 divided doses a day (5)(6)(7). Over time, as amikacin PK-PD became better understood, dosing changed to larger once-daily doses in order to maximize efficacy and limit toxicity (7)(8)(9)(10). Amikacin is an antibiotic that exhibits a concentration-dependent bactericidal activity, and better clinical outcomes were associated with a high free, unbound plasma concentration-to-MIC ratio (fC max /MIC).…”
mentioning
confidence: 99%
“…A study of patients with severe sepsis or septic shock who were treated with amikacin at 25 mg/kg/day showed that only 70% reached peak concentrations of Ͼ64 mg/liter, which would be Ն8 times the susceptibility breakpoint against Enterobacteriaceae according to EUCAST (8 mg/liter) (316); the same dose, however, should be enough for isolates with a MIC of 4 mg/liter to reach the same target (317). An initial dose of 2,500 mg followed by therapeutic drug monitoring has been suggested for patients with body weights of Ͼ40 kg (318,319). Importantly, the peak concentration/MIC ratio has been challenged as the only pharmacokinetic-pharmacodynamic target to be considered for aminoglycosides (320).…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…In the study of Gálvez et al, 6 only 39% of patients with 25 mg/kg and 76% with 30 mg/kg of amikacin reached peak amikacin levels >60 µg/mL. White et al 20 in a retrospective investigation reported that with a higher than approved dose for amikacin (ie, >15 mg/kg/d), only 63.0% and 36.9% of patients in their institution reached the target Cmax/MIC of ≥10 and AUC 24 /MIC of ≥75 respectively, but only 45.3% of their patients were critically ill. 20 Our study revealed that with standard doses of amikacin (ie, 15 mg/kg/d), no patient reached target peak levels. Even in the high-dose group, in less than half of the patients did the amikacin peak concentrations reach the target level (>64 µg/mL).…”
Section: Discussionmentioning
confidence: 96%